THE IMPORTANCE OF IMPLEMENTING SUSTAINABLE TOURISM IN THE GOVERNANCE OF THE RAMBU SOLO' CEREMONY IN TANA TORAJA (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
The Rambu Solo' ceremony is a funeral tradition that is a major attraction of cultural tourism in Tana Toraja. However, the increase in tourist visits poses challenges in preserving indigenous cultural values ​​while still providing economic benefits to the local community. This study aims to analyze the importance of implementing the concept of sustainable tourism in the management of the Rambu Solo' ceremony in Tana Toraja, identify challenges faced in cultural tourism management, and formulate sustainable strategies to maintain cultural authenticity. The study uses a qualitative approach with a literature review method through analysis of journal articles, books, and scientific publications relevant to sustainable tourism and Toraja cultural tourism. The results show that the implementation of sustainable tourism in the Rambu Solo' ceremony can be achieved through three main pillars: cultural preservation by involving traditional leaders in decision-making, economic empowerment of local communities through training local guides and developing craft products, and responsible environmental management by limiting the number of tourists and educating about tourism ethics. The implementation of sustainable tourism requires collaboration between the government, indigenous communities, and tourism stakeholders to maintain a balance between cultural preservation and sustainable economic development.
Keywords: sustainable tourism; Rambu Solo'; cultural tourism; Tana Toraja; cultural preservation